2023
DOI: 10.3390/ijerph20032616
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Pregnancy: Clues and Proof of Adverse Outcomes

Abstract: Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) represents one of the most threatening viral infections in the last decade. Amongst susceptible individuals, infected pregnant women might be predisposed to severe complications. Despite the extensive interest in SARS-CoV-2 research, the clinical course of maternal infection, the vertical transmission and the neonatal outcomes have not been completely understood yet. The aim of our study was to investigate the association between SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Women with preeclampsia should be considered a particularly vulnerable group with regard to the risks posed by COVID-19. 8 showed pregnant women positive for SARS-CoV-2 infection are more likely to develop severe obstetric outcomes; their newborns could have a low birth weight and arterial pH. Vertical transmission seems a rare event, and further investigation is strongly needed.…”
Section: Resultsmentioning
confidence: 99%
“…Women with preeclampsia should be considered a particularly vulnerable group with regard to the risks posed by COVID-19. 8 showed pregnant women positive for SARS-CoV-2 infection are more likely to develop severe obstetric outcomes; their newborns could have a low birth weight and arterial pH. Vertical transmission seems a rare event, and further investigation is strongly needed.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment involved administering vitamin therapy and antipyretics, and a small percentage of patients received anticoagulants. Sessa et al describes in a study that out of the 68 women who tested positive for SARS-CoV-2, 35.29% were symptomatic while 64.71% were asymptomatic [12].…”
Section: Discussionmentioning
confidence: 99%
“…Another major concern about infection is the impact on pregnancy outcome. The risk of adverse pregnancy outcomes were increased, including miscarriage, stillbirth, preterm birth and maternal complications 3,7 . However, alarge Cohort study found that SARS-CoV-2 infection was associated with increased risk of preterm birth only among women infected during late pregnancy 24 .…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…They also found that vertical transmission (3.5%; 95% con dence interval, 2.7−4.7) was rare. Evidence from large cohort and multi-center studies also revealed that vertical transmission was possible but rare 7 . However, most of these data were based on late pregnancy.…”
Section: Introductionmentioning
confidence: 99%